Optically Active H-Phosphinates and Their Stereospecific Transformations into Optically Active P-Stereogenic Organophosphoryl Compounds - Chen, Tieqiao; Han, Li-Biao (Synlett, 2015)
In this account, we summarize our recent work on the preparation of optically active H-phosphinates and their stereospecific transformations, including regio- and stereospecific additions, nucleophilic substitutions with organolithiums and Grignard reagents, halogenation with copper(II) chloride, and dehydrogenative couplings with heteroatom–hydrogen bonds. These reactions provide efficient ways for the synthesis of valuable, optically active, P-stereogenic, organophosphorus compounds from relatively easily prepared, enantiomerically pure, menthyl hydrogen phosphinates. The applications of optically active H-phosphinates in catalytic asymmetric hydrogenations are also discussed.1 Optically Pure Menthyl Hydrogen Phosphinates: Easily Accessible P-Stereogenic Starting Materials2 Optically Pure Menthyl Hydrogen Phosphinates as Starting Materials for the Synthesis of P-Chiral Compounds2.1 Stereospecific Additions2.1.1 Additions to Alkynes2.1.2 Addition to Alkenes2.1.3 Addition to p-Quinones2.1.4 Additions to Ketones or Aldehydes2.2 Stereospecific Nucleophilic Substitution by Organolithiums or Grignard Reagents2.3 Stereospecific Halogenation with Copper(II) Chloride2.4 Stereospecific Cross-Dehydrogenative Coupling with Nucleophiles (Amines, Alcohols, Thiols, etc.)2.5 Stereospecific Cross-Coupling with C–X Bonds3 Asymmetric Catalytic Hydrogenation Reactions with Optically Pure Menthyl Hydrogen Phosphinates as Ligands4 Conclusion
Keywords: H-phosphinates; P-stereogenic organophosphorus compounds; stereoselectivity; transition metals; catalysis; asymmetric hydrogenation; nucleophilic substitutions